Knowledge, Attitude, and Practice Survey among Nurses in Dr. Hasan Sadikin General Hospital toward Tuberculosis-Human Immunodeficiency Virus Collaboration Program - Helen Oktavia Sutiono; Arto Yuwono Soeroto; Bony Wiem Lestari (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: One of the barriers on implementation of Tuberculosis-Human Immunodeficiency Virus (TB-HIV) collaboration is lack of health care workers’ knowledge to this program. This study aimed to measure level of knowledge, attitude, and practice among inpatient nurses in Dr. Hasan Sadikin General Hospital toward TB-HIV collaboration program and to measure their correlation.Methods: This was a cross-sectional study with total sampling method which started on May–October 2013 at Internal Medicine Department ward in Dr. Hasan Sadikin General Hospital. Knowledge, attitude, and practice of research subjects were measured using modified questionnaire about TB-HIV collaboration program, based on guidelines from WHO and National Ministry of Health.Results: Of 88 respondents, there were no respondent had high level, 33 respondents (38%) had moderate level, and 55 respondents (63%) had low level of knowledge toward collaboration. For attitude, 53 respondents (60%) had positive attitude and 35 respondents (40%) had negative attitude. The study also showed 48 respondents (55%) had positive practice and 40 respondents (46%) had negative practice. The correlation between knowledge and attitude, knowledge and practice, and attitude and practice were not statistically significant (p>0.05).Conclusions: The level of knowledge among inpatient nurses in Dr. Hasan Sadikin General Hospital toward TB-HIV collaboration program was low but they showed positive attitude toward the collaboration itself. There was no correlation between knowledge, attitude, and practice among inpatient nurses toward collaboration. Further efforts were needed to improve nurses’ knowledge, attitude, and practice on TB-HIV collaboration.[AMJ.2016;3(1):85–92] DOI: 10.15850/amj.v3n1.715